2014
DOI: 10.1111/tpj.12509
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose metabolism in plants

Abstract: SUMMARYTrehalose is a quantitatively important compatible solute and stress protectant in many organisms, including green algae and primitive plants. These functions have largely been replaced by sucrose in vascular plants, and trehalose metabolism has taken on new roles. Trehalose is a potential signal metabolite in plant interactions with pathogenic or symbiotic micro-organisms and herbivorous insects. It is also implicated in responses to cold and salinity, and in regulation of stomatal conductance and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
422
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(434 citation statements)
references
References 204 publications
(462 reference statements)
11
422
0
1
Order By: Relevance
“…Sugar signaling occurs through pathways involving hexokinase, trehalose-6-phosphate/SnRK1, and TOR, and by direct effects of sugars on growth and metabolism (Rolland et al, 2006;Lunn et al, 2014;Ruan, 2014). In this study, transcriptome analysis revealed that the trehalose phosphate phosphatase TPPI-like gene was expressed at 9-fold higher levels in buds of phyB-1 at 6 DAP and 34-fold higher at 8 DAP.…”
Section: Growth Arrest and Maintenance Of Cell Cycle Gene Expression mentioning
confidence: 81%
“…Sugar signaling occurs through pathways involving hexokinase, trehalose-6-phosphate/SnRK1, and TOR, and by direct effects of sugars on growth and metabolism (Rolland et al, 2006;Lunn et al, 2014;Ruan, 2014). In this study, transcriptome analysis revealed that the trehalose phosphate phosphatase TPPI-like gene was expressed at 9-fold higher levels in buds of phyB-1 at 6 DAP and 34-fold higher at 8 DAP.…”
Section: Growth Arrest and Maintenance Of Cell Cycle Gene Expression mentioning
confidence: 81%
“…The sugar accumulation signature in HL could negatively regulate photosynthesis and Calvin-Benson cycle gene expression (Couée et al, 2006;Supplemental Data Set S3A), as reported in several plant and cyanobacteria species when exposed to high light conditions (Pego et al, 2000;Rolland et al, 2006). In other photosynthetic organisms, sugar accumulation has also been correlated with the down-regulation of peroxisomal lipid b-oxidation (Contento et al, 2004), carotenoid biosynthesis (Ryu et al, 2004), and reactive oxygen species scavenging processes (Stoop et al, 1996;Elbein et al, 2003;Lunn et al, 2014), all phenomena also observed in this work, suggesting a possible role for sugars not only as carbon sinks but also as signaling molecules (Supplemental Note S1).…”
Section: Regulation Of Triose Pentose and Hexose Contentmentioning
confidence: 95%
“…Research involving both Arabidopsis and tomato genes suggested that TREHALOSE PHOSPHATE SYNTHASE11 activity regulates host defense during infestation with green peach aphid by providing a threshold level of signaling trehalose (Singh et al, 2011;Singh and Shah, 2012). However, whether plants regulate trehalose signaling through an internal pool or in response to exogenous addition from insect honeydew remains an open question (Lunn et al, 2014).…”
Section: Insect Secretionsmentioning
confidence: 99%